Structural Planning and Earthquake Resistance of a 4-story office building in Tangerang, Indonesia - Purba, Sadvent Martondang; Wibowo, Kevin Aprilio; Sumantri, Nicholas Anthony (Fakultas Teknik Universitas Tanjungpura, 2025)
Earthquakes are among the natural disasters that pose significant risks to building structures, necessitating meticulous structural planning to minimize the potential for collapse and to safeguard occupant safety. This study examines the structural planning of a four-story office building in Tangerang, Indonesia, emphasizing aesthetics, functionality, and earthquake resistance. The Indonesian National Standards (SNI) conducted the planning process, utilizing SAP2000 software as the primary tool for structural analysis. The adopted methodology includes the application of SNI 1727:2020 for live Load calculations, SNI 1726:2019 for seismic analysis, the DeRuiter and Beringen method for the design of bored pile foundations, and comprehensive structural element modeling using SAP2000. The analysis results indicate that the structural system satisfies the safety requirements, with its capacity exceeding the maximum expected working loads. Although the design approach is conservative, this study recommends optimizing structural element dimensions to enhance cost efficiency. Identified challenges include limitations in SAP2000 modeling capabilities and technical assumptions related to reinforcement placement.